Two interpretations of Aristotle: RobortelIo and Maggi on the theory of comedy - Pueo, Juan Carlos (Tropelías: Review of Literary Theory and Comparative Literature, 1995)
The loss of the second book of Aristotle’s Poetics was one of the most important difficulties for the theorists of comedy on sixteenth century. They only had the authority of Donatus’ rethoric commentary about Terence’s plays, though it wasn’t enough for a poetic perspective, so the first commentarists of Aristotle’s Poetics had to build a theory of their own. But their theories are too dissimilar: Francesco Robortello (1548) attempted to reconstruct an aristotelian theory of comedy starting from the characteristics of tragedy explained in the commentary of the first book; Vincenzo Maggi (1550), on the other hand, preferred to map out the relationships between comedy and laughter, taking into account the aim of the principal dogmas about comedy proposed by Aristotle.